Atemporal Discourse as a Managerial Burden: Implications for Physics Teachers’ Time Management - Januharmen Januharmen; Emayulia Sastria; Dinyah Rizki Yanti Zebua; Ogi Danika Pranata (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
The Merdeka Curriculum idealises the emergence of critical-thinking students. However, when high cognitive demands are present in textbooks, such as the features 'Let's Think Critically!' and 'Let's Discuss!', without transparent time allocation (atemporal), it creates threatening dissonance. This study reveals this paradox: why does idealistic discourse lead to unsupported managerial burdens for Physics teachers? This study aims to critically analyse the implications of the dimension of temporality (instructional time management) in the Merdeka Curriculum Physics textbook for Grade XII Senior High School/MA. Specifically, this study fills a research gap by highlighting the threat of time management uncertainty caused by features that demand high-level cognitive reasoning and discussion, namely 'Let's Reason Critically!' and 'Let's Discuss!'. Using Critical Discourse Analysis (CDA), the primary data sources focused on imperative instructional units that were atemporal (did not specify duration) but demanded complex activities, such as quantitative analysis and evaluation of electrical circuit designs. The results showed a significant dissonance between the textbook's idealistic demands and the minimal managerial support. The 'Let's Think Critically!' and 'Let's Discuss!' features contain high cognitive demands but almost always lack clear time allocations. This gap (Demand Scale 5 vs. Support Scale 1) effectively shifts the burden of operational curriculum and emergency time management to teachers.